NEM SAMBA, NEM RUMBA - de Souza, Eneida Maria (Caderno CRH, 2006)
A partir da figura e da atuação de Carmem Miranda como um símbolo datado do latino-americanismo, são abordados três diferentes momentos das relações culturais entre Estados Unidos e América Latina: a década de 40, o início dos anos 70 e a contemporaneidade, explorando-se tensões e articulações entre a produção intelectual e acadêmica, a experiência histórica da dependência econômica e a cultura de massa. PALAVRAS-CHAVE: Latino-americanismo, dependência cultural, autenticidade nacional, crítica cultural. NEITHER SAMBA, NOR RUMBA Drawing from the image and performance of Carmen Miranda as a dated symbol of Latin Americanism, this paper covers three different momenta of the cultural relationship between the United States and Latin America: the 40s, the early 70s, and contemporary times, exploring the tensions between intellectual and academic production, as well as the historical experience of economic dependence and mass culture. KEYWORDS: Latin-americanism, cultural dependence, national authenticity, cultural criticism. Publicação Online do Caderno CRH: http://www.cadernocrh.ufba.br